Obligation, entitlement and dispute under the English poor laws - Jones, Peter; King, Steven, 1966- (Cambridge Scholars Publishing, 2015)
With its focus on poverty and welfare in England between the seventeenth and later nineteenth centuries, this book addresses a range of questions that are often thought of as essentially "modern": How should the state support those in work but who do not earn enough to get by? How should communities deal with in-migrants and immigrants who might have made only the lightest contribution to the economic and social lives of those communities? What basket of welfare rights ought to be attached to the status of citizen? How might people prove, maintain and pass on a sense of "belonging" to a place?